Love on Lexington Avenue - Layne, Lauren (Gallery Books, 2019)
"It's Primates of Park Avenue meets Lauren Weisberger in this second installment of the delightfully fun, witty, extravagent Central Park Pact series from New York Times bestselling author Lauren Layne."--